Florida Container Mosquitoes - Jorge R. Rey; C. Roxanne Rutledge Connelly (EDIS)
ENY860, a 5-page illustrated fact sheet by Jorge R. Rey and Roxanne Connelly, describes common characteristics of these species of mosquito that develop in water-holding containers, both natural and artificial, major species in Florida, and methods of control. Includes references. Published by the UF Department of Entomology and Nematology, June 2010.